Clinical performance of topical sodium fluoride when supplementing carbamide peroxide at-home bleaching gel - Barcellos, Daphne Camara [UNESP]; Batista, Graziela Ribeiro [UNESP]; Da Silva, Melissa Aline [UNESP]; Pleffken, Patricia Rondon [UNESP]; Valera, Marcia Carneiro [UNESP] (My University, 2015)
This clinical study evaluated the use of 0.11% topical sodium fluoride (SF) desensitizing agent to treat tooth sensitivity during a nightguard tooth whitening procedure. Thirty-two subjects bleached their teeth with 10% carbamide peroxide (CP) gel using an at-home bleaching technique with custom trays. During bleaching treatment, subjects were divided into 2 groups (n = 16). The subjects in Group 1 received a topical gel containing 0.11% SF; the subjects in Group 2 received a placebo gel (PG). Each subject was instructed to place the gel in his/her bleaching tray for 30 min every day following bleaching treatment. Results showed the use of SF did not affect the whitening efficacy of the 10% CP gel. Subjects who received the PG had significantly higher tooth sensitivity when compared with subjects who received SF (P < 0.00). The use of daily 0.11% SF after 10% CP bleaching gel reduced tooth sensitivity during the bleaching treatment.
Keywords: Carbamide peroxide; Dental bleaching; Fluoride; Tooth sensitivity